To simplify the expression \( 2^{-2} \cdot 2^{-2} \), we can apply the property of exponents that states \( a^m \cdot a^n = a^{m+n} \).
Here, we have:
\[ 2^{-2} \cdot 2^{-2} = 2^{-2 + (-2)} = 2^{-4} \]
Now, looking at the multiple-choice answers:
- \( 4^{4} \)
- \( 4^{-4} \)
- \( 2^{-42} \)
- \( 2^{42} \)
We can express \( 2^{-4} \) in a different form to match one of the choices. We know that:
\[ 4 = 2^2 \implies 4^{-4} = (2^2)^{-4} = 2^{-8} \]
None of the options provided match \( 2^{-4} \) directly.
Thus, looking closer at \( 2^{-4} \):
The closest selection that includes \( 2^{-4} \) without altering the base is not available. Therefore, none of the multiple-choice answers match the simplified expression accurately.
To summarize: The expression \( 2^{-2} \cdot 2^{-2} \) simplifies to \( 2^{-4} \). There is no equivalent match in the given options.